RIVER CLIFF REINFORCEMENT EFFORTS BY APPLICATION OF COMBINATION OF DAM STONE, GABION, TETRAPOD, AND BAMBOO FLOW ALIGNER - Dian Eksana Wibowo; Didik Purwantoro; Satoto Endar Nayono; Indra Bayu Wardhana; Yoga Bayu Prabowo (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2020)
The purpose of research : (1) determine the ratio between the combination of retrofitting tetrapod-bamboo alignment-tetrapod (FP1); bamboo flow aligner-tetrapod-bamboo flow aligner (FP2); Check Dam Stones-Gabion-Check Dam Stones (FP3); Gabion-Check Dam Stones-Gabion (FP4)? (2) The effectiveness of the combination of strengthening the tetrapod-bamboo aligner-tetrapod (FP1); bamboo flow aligner-tetrapod-bamboo flow aligner (FP2); Check Dam Stones-Gabion-Check Dam Stones (FP3); Gabion-Check Dam Stones-Gabion (FP4)?Using the experimental method by creating a Labolatorium scale river model. Testing using clay and sand. The test model is a cliff without reinforcement and cliff with a combination of reinforcement between tetrapods; bamboo flow aligner; check Dam stones and Gabions. Testing by flowing water for 180 minutes/3 hours with a constant discharge of 7.07 liters/second, the installation of reinforcement is 51 cm apart.The results showed that (1) In general, the effect of the FP1 reinforcement installation was the variation of the combination that was considered the best in reducing scouring on the cliffs and riverbeds. (2) Variation of the combination of FP1, is more effective in reducing the scouring that occurs. At the beginning of the channel turns from STA 00-06 effectively used tetrapod installation, with scours that occur as big as -5 cm, in the middle of the STA channel 06-16 effectively using the installation of bamboo flow aligner, scours that occur as much as -1.5 cm, whereas at At the end of the turn, STA 17-24 used tetrapod installation, scouring by -3.8cm.Keyword: scouring, bamboo flow aligner, tetrapod.